PENGEMBANGAN MODEL FLIPPED LEARNING PADA MATAKULIAH EKONOMI REGIONAL UNTUK MENINGKATKAN COMPETENCE, CONSCIENCE DAN COMPASSION MAHASISWA PRODI PENDIDIKAN EKONOMI - Martikasari, Kurnia (Jurnal Pendidikan Ekonomi dan Akuntansi, 2021)
This research aims to analyze how developing flipped learning model in Regional Economics course on second semester 2019/2020 can improve competence, conscience and compassion of Economic Education students. This research is a quasi-experimental research. Assessment of competence aspect was obtained by using pretest and post test scores, while for aspects of conscience and compassion by using questionnaires and observations. Results of this research showed that developing flipped learning model in Regional Economics course can improve the competence, conscience and compassion of Economics Education students.Keywords : flipped learning, competence, conscience, compassion and Regional Economics